Aspectuality. An Onomasiological Model Applied to the Romance Languages - Dessì Schmid, Sarah (De Gruyter, 2020)
This synchronic study presents a new onomasiological, frame-theoretical model for the description, classification and theoretical analysis of the cross-linguistic content category aspectuality. It deals specifically with those pieces of information, which, in their interplay, constitute the aspectual value of states of affairs. The focus is on Romance Languages, although the model can be applied just as well to other languages, in that it is underpinned by a principle grounded in a fundamental cognitive ability: the delimitation principle. Unlike traditional approaches, which generally have a semasiological orientation and strictly adhere to a semantic differentiation between grammatical aspect and lexical aspect (Aktionsart), this study makes no such differentiation and understands these as merely different formal realisations of one and the same content category: aspectuality.